1991
DOI: 10.1063/1.105907
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric determination of the optical constants of C60 (Buckminsterfullerene) films

Abstract: We report the first ellipsometric measurement of the fundamental optical constants (n,k) of C60 films deposited on Si(100) and Au overcoated Si(100) substrates. We obtain a highest occupied molecular orbital-lowest unoccupied molecular orbit (HOMO-LUMO) gap value of 2.3 eV, slightly larger than the gap values obtained from the x-ray photoelectron spectroscopy and electron-energy-loss spectroscopy experiments. The structure observed in the UV is discussed in terms of single-electron excitations across the HOMO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
82
0
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(95 citation statements)
references
References 17 publications
9
82
0
4
Order By: Relevance
“…For the two finite nanotubes considered, the polarizabilities per carbon atom, ␣ 0 ͑w 1 ͒ = 3.2 and ␣ 0 ͑w 2 ͒ = 2.45 Å 3 , are of the same order as for the C 60 fullerene, 1.38-1.42 Å 3 per atom. 31 …”
Section: A Binding Energy and Interaction Energy With The External Ementioning
confidence: 99%
“…For the two finite nanotubes considered, the polarizabilities per carbon atom, ␣ 0 ͑w 1 ͒ = 3.2 and ␣ 0 ͑w 2 ͒ = 2.45 Å 3 , are of the same order as for the C 60 fullerene, 1.38-1.42 Å 3 per atom. 31 …”
Section: A Binding Energy and Interaction Energy With The External Ementioning
confidence: 99%
“…Ellipsometry can be used to measure the thickness of the C 6 o films as they are deposited. 28 By variation of the substrate material and crystalline orientation, and by variation of the film growth temperature, the crystallite size and microstructure of the film can be varied. Single crystals can be grown either from solution using solvents such as CS 2 , hexane and toluene, or by vacuum sublimation.…”
Section: Fig 4 (A) Gel Permeation Chromatogram Of Fullerenes Obtainmentioning
confidence: 99%
“…25 in which the transmittance for solid C 6 o is compared with that for C 6 o dissolved in decalin. 28 The optical properties of solid C 6 o and C 70 have been studied over a wide frequency range using the variable angle spectroscopic ellipsometry (VASE) technique. 28 ' 179 From the VASE measurements, the complex refractive index, h(co) = n(a>) + ik(eo), is determined, which is related to the complex optical dielectric function e(co) = €i(w) + ie 2 …”
mentioning
confidence: 99%
“…Coulomb interaction effects on the absorption spectra and the optical nonlinearity have been also studied [8]. We have found that the linear absorption spectra of C 60 and C 70 are well explained by the Frenkel exciton picture [9] except for the charge transfer exciton feature around the excitation energy 2.8 eV of the C 60 solids [2]. Coulomb interaction effects reduce the magnitude of the optical nonlinearity from that of the free electron calculation [8], and thus the intermolecular interaction effects have turned out to be important.…”
mentioning
confidence: 86%
“…A lot of optical experiments have been performed, and excitation properties due to π-electrons delocalized on molecular surfaces have been measured. For example, the optical absorption spectra of C 60 and C 70 [1,2] have been reported, and the large optical nonlinearity of C 60 [3,4] has been found. The absorption spectra of higher fullerenes (C 76 , C 78 , C 84 , etc.)…”
Section: Phason Lines and Linear Absorptionmentioning
confidence: 99%